Dva pogleda na "najtežje razumljivo delo" Leonida Andrejeva - Kralj, Lado (Primerjalna književnost, 2001)
Two views on "the most incomprehensible work" of Leonid Andreyev. - The first part of the article outlines the links between the critical criteria of Josip Vidmar (1895-1992) and his attachment to the work of Leonid Andreyev, primarily to his play, The Black Masks. The second part, based on Bakhtin's theses on carnival culrure, interprets the properties of Black Masks, which were either not seen or understood by Vidmar.
Keywords: Andreev, Leonid; Vidmar, Josip, 1895-1992; ruska književnost; Russian literature; gledališka kritika; literarne študije; Andreev, Leonid: Črne maske